Effects of a novel synbiotics-enzyme complex as a replacement for antibiotics on growth performance, slaughter and meat characteristics, immune organ index, and intestinal morphology of broilers - Zhao, Zihao; Liswaniso, Simushi; Qin, Ning; Cao, Shengxiao; Wu, Xin; Ma, Chang; Yan, Chunchi; Xu, Rifu; Sun, Xue (Frontiers in Veterinary Science, 2024)
IntroductionAntibiotic use in broilers is being discouraged globally due to the challenges it poses. This study was conducted to assess the effects of supplementing broilers with a Symbiotic-Enzyme complex (SEC) containing prebiotics (mannose oligosaccharides), probiotics (Clostridium butyricum and Bacillus subtilis), and enzymes (glucose oxidase, and α-galactosidase) as an alternative to antibiotics on growth performance, carcass and meat quality traits, mortality, linear body measurements, intestinal morphology and immune organ indexes.MethodA total of 864 mixed-sex 1-day-old arbor acres (AA+) broilers were allocated to 8 experimental groups replicated 9 times with 12 chickens per replicate. These included 6 treatment groups with SEC inclusion levels of 0.025, 0.04, 0.05, 0.06, 0.08, and 0.10%, respectively, and two control groups: a negative control group containing a basal diet only and the positive control group (Antibiotics group) containing a basal diet and antibiotic oxytetracycline added at 0.2%. Growth performance was measured on day 21 and 42, and the mortality, carcass, meat quality traits, linear body measurements, intestinal morphology, and organ size indexes were measured on day 42.ResultsThe results indicated that supplementing broilers with 0.1% SEC resulted in insignificant (P > 0.05) increases in average daily feed intake (ADFI), significant (P < 0.05) increases in the average daily gains (ADG), and significant (P < 0.05) reduction in a feed-to-gain ratio (F/G) in all the phases compared to the control and antibiotics groups. Supplementation of broilers with 0.1% SEC inclusion levels also significantly (P < 0.05) increased the body slope length, chest width, chest depth, keel length, and shank circumference. Furthermore, broilers on diets containing 0.1% SEC inclusion level also had significantly (P < 0.05) higher dressed, semi-evisceration, evisceration, and breast muscle percentages. Including SEC at 0.1% also significantly (P < 0.05) increased villus height and villus-to-crypt ratio (V/C) but reduced crypt depth in the duodenum, jejunum, and ileum compared to the control groups. SEC inclusion at 0.1% significantly (P < 0.05) increased the spleen, bursal, and thymus indexes, respectively.ConclusionSupplementation of broilers with 0.1% SEC can be used as an antibiotic alternative because it increases the F/G, improves the carcass and meat quality, increases the body conformation, improves the small intestines' functions, and immune organ size.